2012
DOI: 10.1007/s00246-012-0575-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Iloprost as a Rescue Therapy for Transposition of the Great Arteries With Persistent Pulmonary Hypertension of the Newborn

Abstract: Transposition of the great arteries (TGA) in the newborn combined with persistent pulmonary hypertension was reported previously to occur in 3-12 % of full-term neonates with TGA. Right-to-left shunting at the ductal level causes severe hypoxemia despite prostaglandin infusion and balloon atrial septostomy. Although the introduction of inhaled nitric oxide (iNO) has improved the prognosis, this condition still is associated with high preoperative mortality. This report describes the case of a newborn with TGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…[4][5][6][7] Postnatally, persistant pulmonary hypertension has been reported for some patients. 12,13 Recently, Punn et al 7 reported that hypermobile septum primum and retrograde diastolic flow in the ductus arteriosus can help predict the need for urgent atrioseptostomy. Neonates with transposition of the great arteries and intact ventricular septum need adequate interatrial mixing to reach an acceptable saturation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Postnatally, persistant pulmonary hypertension has been reported for some patients. 12,13 Recently, Punn et al 7 reported that hypermobile septum primum and retrograde diastolic flow in the ductus arteriosus can help predict the need for urgent atrioseptostomy. Neonates with transposition of the great arteries and intact ventricular septum need adequate interatrial mixing to reach an acceptable saturation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In recent years, individual case studies have demonstrated the efficacy of pulmonary vasodilators and extracorporeal membrane oxygenation (ECMO) in the treatment of PPHN in infants with D-TGA, both before and after ASO. 9,10 There is a paucity of data, however, on clinical correlates and short-term outcomes of infants with D-TGA who required inhaled nitric oxide (iNO) and/or ECMO. In the current study, we sought to determine the proportion of neonates with D-TGA who required iNO and/or ECMO at a single center and to compare their clinical characteristics and shortterm outcomes with others who did not require iNO and/or ECMO.…”
Section: -Loop Transposition Of the Great Arteries (D-mentioning
confidence: 99%
“…Inability to wean PGE1 signifies unstable hemodynamics and, in our practice, triggers efforts to categorize the patient into the small subset of patients with TGA and reactive pulmonary vasculature. For these babies, increased awareness is warranted given the association with less a favorable perioperative course [26]. In fact, in our cohort, our only mortality was a patient with pulmonary hypertension after ASO whom we were unable to wean off mechanical circulatory support.…”
Section: Commentmentioning
confidence: 74%